COPING SELF-EFFICACY, PERFECTIONISM, AND BURNOUT AMONG UNIVERSITY STUDENTS DURING COVID-19 PANDEMIC - Mohd. Dahlan Hj. A. Malek; Nurul Izzah Abu Bakar; Ida Shafinaz Mohamed Kamil (Universitas Mercu Buana Jakarta, 2022)
Themainpurposeofthisstudywastoexaminetherelationshipbetweenperfectionism and burnout among university students during the Covid-19 pandemic. This situation had an impact on students which they ought toundergo online distance learning (ODL) from home. Some students may find it difficult to obtain appropriate guidance outside of the normal academic setting. Besides, thisstudy also determines whether coping self-efficacy mediates the relationshipbetween perfectionism and burnout. A sample of 176 University students participated in this study. Survey methods with the use of FrostMultidimensional Perfectionism Scale (FMPS), Maslach Burnout Inventory-Student Survey(MBI-SS), and Coping Self-Efficacy Scale (CSE) were used in this study. The results wereanalyzed using SPSS version 27.0. Bivariate and multiple regression were used to test allhypotheses for this study. The findings of this study show that perfectionistic strivings have a positiverelationshipwithburnout. Meanwhile,perfectionisticconcernshave a negativerelationshipwithburnout.The findingsalsoshowedthatbothperfectionisticstrivings and concerns positively related to coping self-efficacy (mediator). Lastly, theresults also showed that coping self-efficacy could partially mediate the relationshipbetweenperfectionism and burnout.